2012
DOI: 10.2174/157015912799362805
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Metabotropic Glutamate Receptor Modulators

Abstract: Glutamate is the main excitatory neurotransmitter in the central nervous system (CNS) and is a major player in complex brain functions. Glutamatergic transmission is primarily mediated by ionotropic glutamate receptors, which include NMDA, AMPA and kainate receptors. However, glutamate exerts modulatory actions through a family of metabotropic G-protein-coupled glutamate receptors (mGluRs). Dysfunctions of glutamatergic neurotransmission have been implicated in the etiology of several diseases. Therefore, phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 396 publications
(465 reference statements)
1
60
0
1
Order By: Relevance
“…Although it is possible that glutamate formation from NAAG hydrolysis alone may not be enough to lead to the substantial increase in glutamate concentration noted here, increased GCPII expression may worsen the injury in multiple ways, one of which may be by decreasing the levels of neuroprotective NAAG. NAAG activates mGluR3 which plays a strong role in inhibiting presynaptic glutamate release (Hovelso et al, 2012). Since we have measured total glutamate in this study, we do not know what fraction of this glutamate is extracellular.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that glutamate formation from NAAG hydrolysis alone may not be enough to lead to the substantial increase in glutamate concentration noted here, increased GCPII expression may worsen the injury in multiple ways, one of which may be by decreasing the levels of neuroprotective NAAG. NAAG activates mGluR3 which plays a strong role in inhibiting presynaptic glutamate release (Hovelso et al, 2012). Since we have measured total glutamate in this study, we do not know what fraction of this glutamate is extracellular.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate receptors modulate glutamatergic neurotransmission in the brain and play a role in memory, learning and motor control; glutamatergic dysfunction is implicated in a range of neurological disorders [2527]. Two classes of glutamate receptor have been described: ionotropic glutamate receptors (iGlu receptors) [28], and metabotropic glutamate receptors (mGlu receptors) [26].…”
Section: Glutamate Receptors In Parkinson's Diseasementioning
confidence: 99%
“…1014 It has been reported that mGlu 2 is involved in the pathogenesis of numerous brain dysfunctions, including psychiatric disorders and neurodegenerative diseases. 7,1519 Therefore pharmacological modulation of mGlu 2 represents a promising therapeutic approach for the treatment of several CNS diseases, 20 including drug dependence, 2123 chronic pain, 24 anxiety, 17 depression, 25,26 schizophrenia, 27 Parkinson’s disease 28,29 and Alzheimer’s disease. 30 Initial drug discovery efforts focused on non-selective mGlu 2/3 agonists and antagonists that bind to the mGlu orthosteric binding site (evolutionarily conserved glutamate binding site); 31 however, in recent years there has been a shift towards allosteric modulation strategies (consisting of positive and negative allosteric modulators; abbreviated as PAM and NAM, respectively) that offer the potential for improved selectivity for mGlu 2 or mGlu 3 .…”
Section: Introductionmentioning
confidence: 99%